The proton low-mass microquasar: high-energy emission - Romero, Gustavo Esteban (2008)
Context: A population of unidentified gamma-ray sources is forming a structure resembling a halo around the Galactic center. These sources are highly variable, and hence they should be associated with compact objects. Microquasars are objects undergoing accretion with relativistic jets; if such an object has a low-mass, evolved, donor star, it might be found in the Galactic halo. If these low-mass microquasars can generate detectable gamma-ray emission, then they are natural candidates to account for the halo high-energy sources. Aims: We aim to construct models for high-energy emission of low-mass microquasars, which could produce a significant luminosity in the gamma-ray domain. Methods: We consider that a significant fraction of the relativistic particles in the jets of low-mass microquasars are protons and then we study the production of high-energy emission through proton synchrotron radiation and photopion production. Photopair production and leptonic processes are considered as well. We compute a number of specific models with different parameters to explore the possibilities of this scenario. Results: We find that important luminosities, in the range of 1034–1037 erg s−1, can be achieved by proton synchrotron radiation in the Gamma-Ray Large Area Space Telescope (GLAST) energy range, and lower, but still significant luminosities at higher energies for some models. Conclusions: We conclude that the proton microquasar model offers a very interesting alternative to account for the halo gamma-ray sources and presents a variety of predictions that might be tested in the near future by instruments like GLAST, the High-Energy Stereoscopic System II (HESS II), the Major Atmospheric Gamma-ray Imaging Cherenkov telescope II (MAGIC II), and neutrino telescopes like IceCube.